Enhanced photoelectrochemical performance and photocatalytic activity of ZnO/TiO2 nanostructures fabricated by an electrostatically modified electrospinning - Ramos, Pierre G. (2017)
In this work, ZnO/TiO2 nanostructures were fabricated by an electrostatically modified electrospinning technique using zinc acetate and commercially available TiO2-P25, polyvinyl alcohol, and a solvent. The ZnO/TiO2 nanostructures were fabricated on fluorine-doped tin oxide (FTO) glass substrate by electrospinning of aqueous solution containing different amounts of zinc acetate. The TiO2-P25 nanoparticles were immobilized within zinc acetate/PVA nanofibers. The precursor nanofibers obtained were converted into polycrystalline ZnO and ZnO/TiO2 by calcination at 600 °C. The structure and morphology of the obtained nanostructures were characterized by X-ray diffraction and field emission scanning electron microscopy, respectively. It was found that the TiO2-P25 nanoparticles were attached to the ZnO nanostructures, and the mean diameter of the nanoparticles forming the nanostructures ranged from 31 to 52 nm with increasing the amount of zinc acetate. The incident photon-to-current efficiency (IPCE) spectra of the fabricated nanostructures were measured in a three-electrode cell. The photocatalytic activities of ZnO and ZnO/TiO2 nanostructures were evaluated toward the decomposition of methyl orange. The obtained results evidenced that the coupling of TiO2 with ZnO enhanced the IPCE and improved the photocatalytic activity of ZnO. Particularly, the ZnO/TiO2 nanostructures fabricated with a zinc acetate-to-PVA ratio of 2:3 exhibited the highest IPCE and photocatalytic activity.